Differential expression of TLR and CXCR genes in mammary HC11 cells challenged with Bacillus cereus and Bacillus subtilis: Implications for mastitis resistance - Nova Dilla Yanthi; Anneke Anggraeni; Syahruddin Said; Sugiyono Saputra; Retno Damayanti Soejoedono; Muladno Muladno; Nina Herlina; Ima Fauziah; Herjuno Ari Nugroho; Mukh Fajar Nasrulloh; Rida Tiffarent (Veterinary World)
Background and Aim: Mastitis remains a major health challenge in dairy cattle, often caused by Gram-positive pathogens. Toll-like receptors (TLRs) and chemokine receptors (CXCRs) play essential roles in the innate immune response of mammary epithelial cells (MECs). However, the differential expression of these genes in response to specific mastitis-causing Bacillus spp. has not been comprehensively evaluated. This study aimed to characterize the temporal gene expression patterns of TLR and CXCR family members in murine mammary epithelial HC11 cells exposed to Bacillus cereus and Bacillus subtilis, thereby providing insights into their immunological roles in mastitis pathogenesis.